癌症治疗方法 (2024)
本发明内容提供一种用于降低癌症生存力或增强癌症对一抗癌剂的易感性(susceptibility)的方法和制剂。该方法包括对个体投予有效量的抗寄生虫剂和自噬抑制剂。该方法也可额外或非必要地包括向个体投予所述抗癌剂。本发明内容更提供用于治疗癌症，特别是对抗癌剂无反应的癌症的制剂。该制剂包括至少两种选自由抗寄生虫剂、自噬抑制剂和HDAC抑制剂所组成的药剂；以及药学上可接受的赋形剂。 Provided herein are methods and formulations for reducing viability of a cancer or enhancing susceptibility of a cancer to an anti-cancer agent. The method includes administering to the subject an effective amount of an anti-parasitic agent and an autophagy inhibitor to the subject. Additionally or optionally, the method further includes administering to the subject the anti-cancer agent. Also provided herein are formulations for the treatment of cancers, particularly cancers that are unresponsive to anti-cancer agents. The formulation includes at least two agents selected from the group consisting of an anti-parasitic agent, an autophagy inhibitor and an HDAC inhibitor; and a pharmaceutically acceptable excipient.